A cross-sectional study to estimate the prevalence of eating disorders and ascertain factors for eating disorder risk among senior college students in a metropolitan city - Rujuta S. Hadaye; S Rahini (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Eating disorders are more prevalent in Western countries and their prevalence is on the rise in India, mainly due to peer pressure and the influence of media. However, research on eating disorders is limited in India. The aim of this study is to estimate the prevalence of eating disorders among senior college students and to ascertain factors for eating disorder risk. MATERIALS AND METHODS: A cross-sectional study was conducted among 807 students attending 2 of the arts and science colleges in a metropolitan city (Mumbai) over a period of 12 months from June 2019 to June 2020. A predesigned case record form was used to collect information on sociodemographic profiles and other factors related to eating disorder risk. Eating Attitude test (EAT-26) was used as a screening test to find the prevalence of those at risk for eating disorders. Munich-ED quest was used for the diagnosis of the eating disorder. RESULTS: Data were analyzed using SPSS version 16.0. The Chi-square test was used to find the association of various factors with eating disorder risk. Our study found the overall proportion of eating disorder risk to be 42.25%. Among them, 19 (2.35%) individuals had night eating syndrome and 7 (0.86%) had binge eating syndrome as per DSM-5 criteria using Munich ED Quest. On logistic regression, we found fasting once or twice a week (OR: 2.916;95%CI: 1.524-5.574; P = 0.001), increase in duration of physical activities for more than 10 h a week (OR: 3.874; 95% CI: 2.200-6.821; P < 0.001), being commented for weight by friends/relatives (OR: 1.695; 95% CI: 1.244-2.309; P = 0.001), and thought of being overweight (OR: 1.763;95% CI: 1.178-2.639; P = 0.006) to be significantly associated with risk of eating disorders. The age group of 18-20 years (OR: 0.519;95%CI: 0.345-0.782; P = 0.002) was found to be at lower risk for eating disorders compared to the 22-24 year age group. CONCLUSION: Screening of students with a simple tool like EAT-26 would prove beneficial in the early identification of those at risk of eating disorders.